The Relationship Between Flexing Behavior and The Formation of Personal Branding of Sisca Kohl on Instagram Account @siscakohl - Ritonga, Dai Ridho; Ananda, Sofiari (CONTENT: Journal of Communication Studies, 2024)
This research entitled "The Relationship Between Flexing Behavior and the Formation of Personal branding of Sisca Kohl on Instagram Account @siscakohl." The research method used is quantitative correlational. The purpose of this research is to determine the relationship between Flexing Behavior and the formation of Sisca Kohl's Personal branding on the @siscakohl Instagram account. The theories used in this study consist of Mass Communication, New Media, Social Media, Instagram, Personal branding, Thorstein Veblen's Theory of Consumption. The population of this research consists of all followers of @siscakohl Instagram account, which total amounts 1,617,781 people. The sample total amounts is 100 people which determined by using the Slovin formula with a precision of 10% and a confidence level of 90%. This research applies purposive sampling technique. Data collection is done by distributing online questionnaires through Google Form. The researcher conducted a series of data analysis techniques, including validity test, reliability test, single table analysis, cross-tabulation analysis, and Spearman rho hypothesis test. The hypothesis test shows that H0 is rejected and Ha is accepted, indicating that there is a relationship between Flexing Behavior and the formation of Sisca Kohl's personal branding on the @siscakohl Instagram account. Furthermore, with a correlation coefficient value of 0.342, it indicates a low but significant relationship between the two variables. Through the determinant correlation test, it is known that Flexing Behavior influences 12% of the formation of Sisca Kohl's personal branding on the @siscakohl Instagram account.